2021
DOI: 10.1007/s12011-021-02580-x
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effects of Copper Sources and a High Level of Phytase in Phosphorus-Deficient Diets on Growth Performance, Nutrient Digestibility, Tissue Mineral Concentrations, and Plasma Parameters in Nursery Pigs

Abstract: The present study investigated the interactive effects of copper sources and a high level of phytase on growth performance, nutrient digestibility, tissue mineral concentrations, and plasma parameters in nursery pigs. Weaning piglets (N = 192; 6.06 ± 0.99 kg), blocked by body weight, were randomly allotted to 1 of 4 dietary treatments, with 12 pens per treatment and 4 pigs per pen. A basal diet for each phase was formulated to meet nutrient requirements for nursery pigs with the exception that standardized tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…At pH 6.5, the decreases were even more marked but were almost non-existent at pH 2.5. The most likely explanation for these observations would be formation of insoluble phytic acid-Cu complexes at higher pH, which is of some concern given the pH of the porcine gut (116)(117)(118). In pigs weighing 6-22 kg, P digestibility was greater with methionine-chelated Cu than with Cu sulfate (118).…”
Section: 106) After 2 H In Contactmentioning
confidence: 99%
See 1 more Smart Citation
“…At pH 6.5, the decreases were even more marked but were almost non-existent at pH 2.5. The most likely explanation for these observations would be formation of insoluble phytic acid-Cu complexes at higher pH, which is of some concern given the pH of the porcine gut (116)(117)(118). In pigs weighing 6-22 kg, P digestibility was greater with methionine-chelated Cu than with Cu sulfate (118).…”
Section: 106) After 2 H In Contactmentioning
confidence: 99%
“…The most likely explanation for these observations would be formation of insoluble phytic acid-Cu complexes at higher pH, which is of some concern given the pH of the porcine gut (116)(117)(118). In pigs weighing 6-22 kg, P digestibility was greater with methionine-chelated Cu than with Cu sulfate (118). Chelated Cu would be more stable in the upper gastrointestinal tract and less available to form complexes with phytic acid; thus there would be a better release of absorbable phosphate (116,119).…”
Section: 106) After 2 H In Contactmentioning
confidence: 99%
“…Min et al (2018) showed zincmethionine hydroxy analog chelate (Zn-MHAC) could improve eggshell quality and promoting Zn and calcium (Ca) deposition in eggshells in laying hens. Ren et al (2021) founded that Cu-MHAC led to greater growth rate in nursery pigs than CuSO 4 in the presence of phytase supplementation. In addition to consideration in animal health, it is important to consider the effects of trace minerals on meat quality as consumers are increasingly concerned about the nutritional value and sensory value of pork.…”
Section: Introductionmentioning
confidence: 99%
“…The following supporting information can be downloaded at: , Table S1: Database used in meta-analysis approach of copper fonts and levels supplemented in nursery piglet’s diets [ 10 , 11 , 29 , 30 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 ,…”
mentioning
confidence: 99%